2023
DOI: 10.3389/fimmu.2023.1184956
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Favorable outcome of allogeneic hematopoietic stem cell transplantation in SARSCoV2 positive recipient, risk-benefit balance between infection and leukemia

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) in SARS-CoV-2 positive candidates is usually delayed until the clinical resolution of the infection’s symptoms and a negative nasopharyngeal molecular test. However, prolonged SARS-CoV-2 positivity has been frequently observed in haematological malignancies, thus representing a challenge for the timing of transplant procedures. Here, we report on the case of a 34-year-old patient with recent pauci-symptomatic COVID-19 undergoing transplant for high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…43 However, in cases where delaying chemotherapy or transplantation could adversely affect leukemia prognosis, especially in high-risk refractory cases, treatment may be initiated once COVID-19 symptoms have subsided, and viral load has decreased. 44 The clinical significance of profound and prolonged neutropenia on COVID-19 mortality in AL patients remains debated. One study identified neutropenia both before and after SARS-CoV-2 infection as an independent risk factor for increased mortality.…”
Section: 3mentioning
confidence: 99%
“…43 However, in cases where delaying chemotherapy or transplantation could adversely affect leukemia prognosis, especially in high-risk refractory cases, treatment may be initiated once COVID-19 symptoms have subsided, and viral load has decreased. 44 The clinical significance of profound and prolonged neutropenia on COVID-19 mortality in AL patients remains debated. One study identified neutropenia both before and after SARS-CoV-2 infection as an independent risk factor for increased mortality.…”
Section: 3mentioning
confidence: 99%